The practices of isolating tuberculosis infectious patients at hospitals of Vhembe district, Limpopo Province - Takalani G. Tshitangano (AOSIS, 2014)
Background: Airborne infections pose a serious threat to susceptible individuals whenever they are together in confined spaces with patients coughing up tuberculosis (TB) bacilli. In healthcare facilities, those with infectious TB should, as far as possible, be isolated from non-infectious patients in order to prevent exposure to the infectious droplet nuclei generated by infected patients. Aim: This article aims to describe the use of masks and isolation of infectious TB patients at hospitals of Vhembe district, Limpopo Province in order to inform future policy and practices. Setting: This study was conducted at seven of the eight hospitals in Vhembe district. Methods: A cross-sectional qualitative design of a descriptive nature was used. Purposive sampling was used to select 57 focus group participants. Necessary approval, permission and clearance were obtained. The participants' rights were respected. Results: This study confirmed that TB cubicles were not reserved for patients with infectious TB and that many TB inpatients at hospitals of Vhembe district were not isolated; masks were not used consistently or appropriately by patients, staff or visitors. Furthermore, the movement of TB inpatients in isolation was not restricted. Conclusions: There is an unnecessary risk of becoming infected with TB at the rural hospitals of Vhembe district as a result of incorrect isolation practices. The development and implementation of a quality control programme, as well as ongoing training at the hospital level, would improve the TB infection control measures practised by healthcare workers at hospitals in Vhembe district and reduce the risk of acquiring TB at these hospitals.